2016
DOI: 10.1021/acsnano.5b06958
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Ion Intercalation Mechanism in MXene Nanosheets

Abstract: MXene, a family of layered compounds consisting of nanosheets, is emerging as an electrode material for various electrochemical energy storage devices including supercapacitors, lithium-ion batteries, and sodium-ion batteries. However, the mechanism of its electrochemical reaction is not yet fully understood. Herein, using solid-state (23)Na magic angle spinning NMR and density functional theory calculation, we reveal that MXene Ti3C2Tx in a nonaqueous Na(+) electrolyte exhibits reversible Na(+) intercalation/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
338
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(374 citation statements)
references
References 60 publications
24
338
1
3
Order By: Relevance
“…Furthermore, only few MXene materials have been used for SIB anodes, such as Ti 3 C 2 T x as shown in Figures 3i-3k. 78 This study further reports that a small fraction of Na + remains in the structure of MXenes event after full desodiation, resulting in the increase in interlayers distance from 9.7 Å to 12.5 Å. 78 This is because the trapped Na + , in conjunction with penetrated solvent molecule lead to expansion of interlayer distance during the initial cycles of sodiation-desodiation by pillaring and swelling mechanisms.…”
Section: Energy Storage Applications Of Mxenessupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, only few MXene materials have been used for SIB anodes, such as Ti 3 C 2 T x as shown in Figures 3i-3k. 78 This study further reports that a small fraction of Na + remains in the structure of MXenes event after full desodiation, resulting in the increase in interlayers distance from 9.7 Å to 12.5 Å. 78 This is because the trapped Na + , in conjunction with penetrated solvent molecule lead to expansion of interlayer distance during the initial cycles of sodiation-desodiation by pillaring and swelling mechanisms.…”
Section: Energy Storage Applications Of Mxenessupporting
confidence: 54%
“…78 This study further reports that a small fraction of Na + remains in the structure of MXenes event after full desodiation, resulting in the increase in interlayers distance from 9.7 Å to 12.5 Å. 78 This is because the trapped Na + , in conjunction with penetrated solvent molecule lead to expansion of interlayer distance during the initial cycles of sodiation-desodiation by pillaring and swelling mechanisms. Further structural change in layered MXenes was not observed upon subsequent sodiation-desodiation cycles, resulting in good capacity retention.…”
Section: Energy Storage Applications Of Mxenessupporting
confidence: 54%
“…This high performance was attributed to the increased number of intercalation sites and large interlayer spacing of 9.8 Å which allow for the double-layer intercalation mechanism [153]. Solid-state NMR and XRD analyses demonstrated that the interlayer distance expands in the first sodiation process by 2.8 Å [154]. It was found that such significant interlayer expansion is caused by both Na + ion intercalation and electrolyte solvent penetration.…”
Section: Transition Metal Carbides and Carbonitridesmentioning
confidence: 99%
“…The mechanism of sodium intercalation into Ti 3 C 2 T x electrode was investigated using aberration-corrected scanning transmission electron microscopy [153] and solid-state 23 Na magic angle spinning NMR spectroscopy [154]. The atomic scale study by STEM showed that double layer of Na + ions can accommodate within the Ti 3 C 2 T x interlayer space upon deep discharge down to 0.0 V vs. Na/Na + ( Figure 14(e) and (f)).…”
Section: Transition Metal Carbides and Carbonitridesmentioning
confidence: 99%
See 1 more Smart Citation